Managerial economics : theory and applications for decision making - Peppers, Larry C.; Bails, Dale. (Englewood Cliffs, N.J. : Prentice-Hall, 1987)
This book builds on a solid base of economic theory and gives expanded coverage of applied microeconomic business techniques and explicit coverage of the linkages between theory and actual business practices. It also examines problems associated with organisations in a quasi-capitalistic environment.
Includes bibliographical references and index.
asm 23/01/19
Loans
Keywords: Managerial economics